Features of gas exchange of healthy people of working age - Noreiko S.B (Kharkov National Pedagogical University, 2011)
The purpose of this study was to improve the accuracy of determining the basal metabolism of healthy people. Comparative studies of basal metabolism of healthy men and women on probation and respiratory physical factors are considered. Surveyed 30 healthy men and women aged 21-56 years. Determination of the volume of absorbed oxygen and produces carbon dioxide carried by the gas analyzer "Spirolit-2" were defined. Calculate the actual respiratory rate. It is established that the actual value of basal metabolism is characterized by low dispersion and higher accuracy.